(untitled) (Journal of Science and Technology, 2016)
On January 13, 1993, in Paris, 130 countries signed the Chemical Weapons Convention (CWC ). The CWC will Note development, production, acquisition, stock piling, retention and direct or indirect transfer of Chemical Weapons (CW). It also prohibits the use or preparation for use of CW and the assistance, encouragement, or induce meet of anyone else to engage in activities prohibited by the CWC. A chemical weapons system consists of several components. A chemical weapon carrier is usually re-quired, e.g., an aircraft, in order to weapon the ammunition to the target. CWC ammunition, which may consist of a bomb or an artillery shell, contains the active chemical ingredient, the CW agent. About 70 different chemicals have been used or stockpiled as CW agents during the 20th century Today, only a few of these are considered of interest o wing to a number of demands that must be placed on a substance if it is to be of use as a CW agent This paper gives a description of the major chemical warfare agents of interest today.